MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA DINI MELALUI KEGIATAN MELUKIS MENGGUNAKAN BENANG PADA KELOMPOK A TAMAN KANAK-KANAK ALIF ISLAMIC PRESCHOOL CENTRE DESA CIAMIS KECAMATAN CIAMIS KABUPATEN CIAMIS - Ai Risnawati Fauziyah (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
This research is motivated by the lack of fine motor skills of children. Children's ability to improve fine motor skills is still low. Less variety of teachers in providing learning. Teachers still use the lecture method. Still using LKA. The purpose of classroom action research is to improve children's fine motor development through painting using threads. To know the learning process. To assess the improvement of fine motor development outcomes in early childhood. The type of research conducted is classroom action research. A study that aims to improve the quality of learning in the classroom and improve the learning process carried out this research was carried out in Group A TK Alif Islamic Preschool Center Ciamis. The number of students is 5 people. 3 girls 2 boys. Research data through observation and interviews. Data collection techniques were carried out by means of observation and documentation. The research was carried out in two cycles, namely cycle I and cycle II. In cycle II, the children's fine motor skills increased.